Contraception in the Developing World: Special Considerations - Schivone, Gillian B.; Blumenthal, Paul D. (Seminars in Reproductive Medicine, 2016)
The United States Agency for International Development (USAID) estimates that there are 225 million women and girls with unmet contraceptive need yearly. Unmet need for contraception is defined as women who desire a delay in childbearing and are not using a modern method of contraception. It is projected that providing contraception to these women would avert 36 million abortions, 70,000 maternal deaths, and 52 million unintended pregnancies overall. In the past 30 years, there has been an increase both in population and in contraception use in the developing world. As a result, it is estimated that in 2015 there were 500 million contraceptive users in developing countries, which is nearly double the prevalence in 2000. Unfortunately, women and girls in developing nations still face many obstacles in obtaining modern methods of contraception. Particular challenges in the developing world include lack of access due to inadequate number of trained providers, fewer method options, and “stock-outs” of contraceptive supplies. Innovative strategies for decreasing unmet need will have to address these challenges, and will necessarily involve programmatic solutions such as community-based distribution and social marketing campaigns. Additionally, increasing uptake of long-acting reversible contraceptive methods will be essential for achieving the goal of decreasing unmet need.
Keywords: contraception; unmet need; LARC; task shifting; developing countries